2015
DOI: 10.1093/alcalc/agv092
|View full text |Cite
|
Sign up to set email alerts
|

More than Light Alcohol Consumption Predicts Early Cessation from Employment in French Middle-Aged Men

Abstract: Our results provide evidence of a dose-effect relationship between alcohol consumption and early work cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Current moderate drinkers have been shown to self-report and objectively be in a better health compared to and heavy drinkers [ 80 , 81 , 82 ], but confounding may occur on the inclusion (or exclusion) of abstainers that might have decreased their level of alcohol consumption due to ill health or due to problems with alcohol [ 83 ]. Research has also shown a negative association between heavy drinking and employment status [ 84 , 85 , 86 ], and a dose-effect relationship between alcohol consumption and early work cessation due to death, disability and early retirement, with retirement before the age of 55 being the most common cause [ 87 ]. Concerning stratified analysis, previous studies have confirmed that people with lower level of education that were working in low-skilled jobs before economic recession were the more frequently unemployed during the harder recession years in Spain and Finland [ 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current moderate drinkers have been shown to self-report and objectively be in a better health compared to and heavy drinkers [ 80 , 81 , 82 ], but confounding may occur on the inclusion (or exclusion) of abstainers that might have decreased their level of alcohol consumption due to ill health or due to problems with alcohol [ 83 ]. Research has also shown a negative association between heavy drinking and employment status [ 84 , 85 , 86 ], and a dose-effect relationship between alcohol consumption and early work cessation due to death, disability and early retirement, with retirement before the age of 55 being the most common cause [ 87 ]. Concerning stratified analysis, previous studies have confirmed that people with lower level of education that were working in low-skilled jobs before economic recession were the more frequently unemployed during the harder recession years in Spain and Finland [ 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that heavy alcohol drinkers [2, 10, 1921], problem drinkers [2, 19, 22] and non-drinkers [20, 22, 23] are more likely to retire on health grounds compared to moderate drinkers; the latter group thought to include former heavy drinkers who may have stopped drinking for health reasons. Evidence from twin studies suggests that these effects are independent from shared environmental and genetic determinants of health behaviour [1, 2].…”
Section: Introductionmentioning
confidence: 99%